Organisasi Luar Sekolah untuk Peningkatan Karakter (Studi Kasus di IPNU IPPNU Ranting Ngreco Kota Kediri) - Agus Miftakus Surur; Aulia Rahmawati (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2018)
AbstractIn exposure, research results contain the task and analysis on the role of school organization in the formation of character as well as how organizations in the creation of the character of teenagers so good character, noble character, as well as ethical sublime. Positive activities organized by Executive Board members, the characters can be formed. The activities of community members become entwined and creating togetherness. Furthermore, in the activity-there are also IPPNU IPNU activities prayer in congregation and completing the Qur'an that is religious. It can foster the religious nature of the members. Organizational behavior is defined as the study of human behavior in organizations that use the science about how human beings act in organizations. This organizational behavior basing on analysis of the human at going so helpful to others. Keywords: Organization, overseas schools, characters, and IPNU IPPNU AbstrakDalam pemaparan hasil penelitian berisikan pendiskripsian dan analisis mengenai peran organisasi luar sekolah dalam pembentukan karakter serta cara organisasi dalam pembentukan karakter remaja agar berkarakter baik, berakhlak mulia, serta berbudi pekerti luhur. Kegiatan-kegiatan positif yang diselenggarakan oleh pengurus, karakter anggota dapat terbentuk. Kegiatan tersebut kebersaaman antar anggota menjadi terjalin dan terciptalah ukhuah. Selain itu dalam kegiatan IPNU-IPPNU juga terdapat kegiatan sholat berjamaah dan khataman Qur’an yang bersifat keagamaan. Hal ini dapat menumbuhkan kerelegiusan anggota. Perilaku keorganisasian di definisikan sebagai studi mengenai perilaku manusia dalam organisasi yang menggunakan ilmu pengetahuan tentang bagaimana manusia bertindak dalam organisasi. Perilaku organisasi ini mendasarkan pada analisis terhadap manusia yang di tujukan bagi ke manfaatan orang.Kata Kunci: Organisasi, Luar Sekolah, Karakter, dan IPNU IPPNU.